Sex-Specific Impact of Ischemic Preconditioning on Tissue Oxygenation and Maximal Concentric Force - Paradis-Deschênes, Pénélope; Joanisse, Denis R.; Billaut, François (Frontiers in Physiology, 2017)
Prior peripheral hypoxia induced via remote ischemic preconditioning (IPC) can improve physical performance in male athletes through improved O2 delivery and utilization. Since females may have an innate protective mechanism against ischemia-reperfusion injury, and since muscle metabolism during contraction differs between sexes, it is relevant to examine the impact of sex in response to IPC to determine whether it is also ergogenic in females. In a randomized, crossover, single-blind study, we investigated muscle performance, hemodynamic and O2 uptake in strength-trained males (n=9) and females (n=8) performing five sets of 5 maximum voluntary knee extensions on an isokinetic dynamometer, preceded by either IPC (3x5-minutes ischemia/5-minutes reperfusion cycles at 200 mmHg) or SHAM (20 mmHg). Changes in deoxy-hemoglobin (Δ[HHb], expressed in percentage of arterial occlusion and considered an index of O2 extraction), and total hemoglobin (Δ[THb]) concentrations of the vastus lateralis muscle were continuously monitored by near-infrared spectroscopy. The metabolic efficiency of the contractions was calculated as the average force/Δ[HHb]avg ratio. Cohen’s effect sizes (ES) ± 90% confidence limits were used to estimate IPC-induced changes and sex differences. IPC increased total muscular force in males only (13.0%, ES 0.64, 0.37;0.90), and this change was greater than in females (10.4% difference, ES 0.40, 0.10;0.70). Percent force decrement was only attenuated in females (-19.8%, ES -0.38, -0.77;0.01), which was clearly different than males (sex difference: ES 0.45, -0.16;1.07). IPC also induced different changes between sexes for average muscle O2 uptake in set 2 (males: 6.4% vs females: -16.7%, ES 0.21, -0.18;0.60), set 3 (males: 7.0% vs females: -44.4%, ES 0.56, -0.17;1.29), set 4 (males: 9.1% vs females: -40.2%, ES 0.51, -0.10;1.13), and set 5 (males: 10.2% vs females: -40.4%, ES 0.52, -0.04;1.09). However, metabolic efficiency was not meaningfully different between conditions and sexes. IPC increased muscle blood volume (↑[THb]) at rest and during recovery between sets, to the same extent in both sexes. Despite a similar IPC-induced initial increase in O2 delivery in both sexes, males displayed greater peripheral O2 extraction and greater strength enhancement. This ergogenic effect appears to be mediated in part via an up regulated oxidative function in males. We conclude